Evaluation Of Fish Waste As Starting Material For Producing Biodegradable Protein-Based Thermoplastic Polymers - Jouti, herylyn (Universiti Sains Malaysia, 2017)
The main objective of the current work was to investigate the suitable processing methods to produce protein based thermoplastic from fish waste, as well as factors that influenced the thermal, morphology, physical and mechanical properties of the protein based thermoplastic from fish waste. Two samples have been used which is fish fillet and fish waste. The protein samples were produced using twin screw extruder, internal mixer and single screw extruder and the properties were characterized. Thermal properties of the fish thermoplastics were determined using DSC and TGA by measuring the decomposition temperature and glass transition temperature (Tg). Morphology of the fracture surface of the protein thermoplastics samples was characterized using SEM. FTIR and tensile tester were used to identify the physical and mechanical properties obtained. It was found that fish fillet had the highest tensile strength compared to fish waste. The glass transition temperature was reduced as the water content increase. The TGA results show that the thermal stability of the fish fillet is higher that fish waste. Evidence from the SEM revealed that the most suitable processing method for fish waste is twin screw extruder. Twin screw extruder shows a better homogeneity than single screw extruder and internal mixer. Twin screw extruder also show pull out matrix which show a better mechanical properties and thermal properties than the two other processing method.